Exploring grief : towards a sociology of sorrow - Jacobsen, Michael Hviid, 1971-; Petersen, Anders, 1973- (London : Routledge, 2019)
As modern society's routine sequestration of death and grief is increasingly replaced by late-modern society's growing concern with existential issues and emotionality, this book explores grief as a social emotion, bringing together contributions from scholars across the social sciences and humanities to examine its social and cultural aspects. Thematically organised in order to consider the historical changes in our understanding of grief, literary treatments of grief, contemporary forms of grief and grief as a perspective from which to engage in critique of society, it provides insights into the sociality of grief and will appeal to scholars of sociology, social theory and cultural studies with interests in the emotions and social pathologies.
"As modern society's routine sequestration of death and grief is increasingly replaced by late-modern society's growing concern with existential issues and emotionality, this book explores grief as a social emotion, bringing together contributions from scholars across the social sciences and humanities to examine its social and cultural aspects. Thematically organised in order to consider the historical changes in our understanding of grief, literary treatments of grief, contemporary forms of grief and grief as a perspective from which to engage in critique of society, it provides insights into the sociality of grief and will appeal to scholars of sociology, social theory and cultural studies with interests in the emotions and social pathologies"--
10 The medicalization of grief11 Suffocated grief, resilience and survival among African American families; 12 Grief in an individualized society: a critical corrective to the advancement of diagnostic culture; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General; Bereavement -- Social aspects; Grief -- Social aspects; Emotions -- Sociological aspects; Bereavement in literature; Grief in literature